(3CSGSjGJ Yde GdCMjGAs - (3GdSYOj, MSjf Ydjs ((3YeGf, GdCQOf (B:s (3OGQ GdjGRhQj GdYdejI ddfTQ hGdJhRjY,s, 2006)
(3ebOeI aj Yde GdCMjGA(B.s
(3HHdjhLQGajI (B: (3U(B. 523-528.s
(3GdSfGfj(B.s
1.
Keywords: (3Yde GdCMjGAs